Republic of Slovenia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that domestic demand in Slovenia rebounded strongly in 2003 after three anemic years. All components of domestic demand strengthened appreciably, fueled by declines in interest rates and the associated pickup in bank credit to the private sector. Progress with disinflation was better than expected. Year-over-year inflation declined from 7.2 percent at end-2002 to 3.5 percent in March 2004. IMF staff analysis suggests that the widening of the output gap associated with the economic slowdown was the dominant driving force behind disinflation in 2003.